The Cosmic Dark Matter Fractal Field Theory Reveals an Explanation for Quantum Healing by Plank Flowmotion of Morphogenetic Fields Enhanced through Heart-Brain Coherence Meditation Techniques (Global Journal of Science Frontier Research, 2020)
The process of biologic Morphogenesis of all life forms as well as some inorganic structures has been studied and examined by many in science. Each investigation arriving at descriptions of the wonder and beauty of nature’s art work and evolutionary resilience but without description of the process of the ability of natural blueprints’ to repeat form and function or how evolution modifies those blueprints’ to accommodate environmental changes to increase survival success of many life forms. The method by which nature reproduces with such repetitive and reparative accuracy of the form and function of a vast variety of organisms known to exist, as well as, certain inorganic forms such as crystals and other well-known shapes of occupied space has eluded science. There is now, however, an emerging theory that reveals a natural process which explains this mystery of nature!